Highly aligned and crystalline poly(3-hexylthiophene) thin films by off-center spin coating for high performance organic field-effect transistors - Chaudhary V.; Pandey R.K.; Prakash R.; Kumar N.; Singh A.K. (My University, 2025)
Controlling the morphology, molecular packing and alignment of conjugated polymer remain a primary challenge that hinders their widespread applications in electronic and optoelectronic devices. Here, we have demonstrated an extremely simple and effective strategy for nucleation and growth of highly crystalline and aligned nanowires of regioregular poly (3-hexylthiophene) (P3HT) in the solvent that exhibits a remarkable enhancement in charge transport properties. We have used the combination of marginal solvent (dichloromethane) and ultrasonication to obtain highly crystalline, aligned and ordered nanowires of P3HT by means of off-center spin coating and compared with their on-center counterparts also. Macroscopically ordered and aligned nanowires of P3HT are confirmed by atomic force microscopy (AFM) and polarized optical microscopy (POM). Grazing incidence X-ray diffraction (GIXD) and high-resolution transmission electron microscopy (HR-TEM) demonstrated highly crystalline π–π stacked lamellar structure. The organic field-effect transistors (OFETs) based on highly oriented and crystalline P3HT nanowires exhibited a 50-fold enhancement in charge carrier mobility (average mobility 0.053 cm2V−1s−1) compared to OFETs based on P3HT film prepared in a good solvent (chloroform), measured under the ambient condition. The results are further supported by UV–vis spectroscopy, cyclic voltammetry, and theoretical calculation. Our study is a promising strategy for achieving large-scale aligned nanostructures of solution processable conjugated polymer film to enable high-performance organic electronic devices. © 2019 Elsevier B.V.